Evaluation of pumice for development of low-cost and energy-efficient composite phase change materials and lab-scale thermoregulation performances of its cementitious plasters. (15th September 2020) - Sarı, Ahmet; Hekimoğlu, Gökhan; Tyagi, V.V.; Sharma, R.K.
Abstract: Integration of a building mass with a phase change-energy storage material is able to improve its thermal efficiency. With this respect, pumice was evaluated as low-cost supporting material for development of energy-efficient composites containing capric acid (CA) and polyethylene glycol(PEG) as phase change material (PCM). The developed leak-proof composites was also incorporated separately with ordinary cement (OC; Portland Cement) to produce novel plaster with thermal energy storage (TES) ability for thermoregulation of buildings. The DSC analysis results demonstrated that the shape-stabilized composite PCMs (S-SCPCMs) had melting temperatures of 31.03 °C and 8.80 °C and TES capacity of 116.27 J/g and 98.39 J/g, respectively. Cycling thermal degradation stability and TES dependability of the leak proof composites were examined by TGA techniques. The lab-scale test revealed that the indoor center temperatures (ICT) of the cubic chambers plastered separately by pumice/CA/OC and pumice/PEG/OC mortars were maintained at comfortable temperature range for relatively longer times compared to the control chamber plastered by OC mortar. Highlights: The pumice/CA(62 wt%) and pumice/PEG(56 wt%) were fabricated as S-SCPCMs. The S-SCPCMs have melting temperature of 8.80 and 31.03 °C, respectively. The S-SCPCMs have relatively high TES capacity of 98.39 and 116.27 J/g, respectively. The S-SCPCMs have good thermal durability and cycling chemical/thermal stability. The S-SCPCM/cement plasters showed remarkable thermoregulation performance.